The Effect of the UK Coordinating Centre for Cancer Research Anal Cancer Trial (ACT1) on Population-based Treatment and Survival for Squamous Cell Cancer of the Anus. Issue 12 (December 2015) - Downing, A.; Morris, E.J.A.; Aravani, A.; Finan, P.J.; Lawton, S.; Thomas, J.D.; Sebag-Montefiore, D.
Abstract: Between 1987 and 1994, three randomised phase III trials showed that chemoradiotherapy with mitomycin C and 5-fluorouracil was superior to radiotherapy alone (ACT1, European Organization for Research and Treatment of Cancer) or radiotherapy with 5-fluorouracil (Radiation Therapy Oncology Group 87-04, Eastern Cooperative Oncology Group 1289) for squamous cell carcinoma of the anus. We explored the population-based changes in England before, during and after the UK-based ACT1 trial. Information was extracted from the National Cancer Data Repository on patients diagnosed with squamous cell anal cancer in England between 1981 and 2010 ( n  = 11 743). Robust treatment information was available for the Yorkshire region ( n  = 1065). Changes in treatment patterns and 3 year survival were investigated in 7 year cohorts before, during and after the ACT1 trial. In Yorkshire, the proportion of patients receiving surgery alone fell from 61.6% before, 29.8% during and 12.5% after ACT1; the proportion of patients receiving primary chemoradiotherapy rose from 6.5% before, 17.7% during and 58.8% after ACT1 and continued to rise to 70.3% in the subsequent period. Three year survival improved during the study period from 59.5% (95% confidence interval 56.6–62.2) before ACT1 to 73.6% (95% confidence interval 71.9–75.2) after the trial. Survival in Yorkshire was comparable with that in England. The treatment for squamous cell carcinoma of the anus changed dramatically during the study period. The predominant use of surgery before ACT1, a transition phase during the trial and a dramatic increase in the use of chemoradiotherapy after ACT1 provide strong evidence of the effect of the trial on population-based practice. Survival continued to increase during this period. Highlights: Changes in anal cancer treatment before, during and after the ACT1 trial were explored. The proportion of patients receiving surgery alone was 62% before the trial and 13% afterwards. The proportion of patients receiving primary chemoradiotherapy rose from 7% to 59%. Survival from anal cancer has increased during the same period. The results provide strong evidence of the effect of the trial on population-based practice.